Gender equality and the advancement of women into senior management positions : assessing the perceptions of the diversity and gender initiatives section of the City of Cape Town - Dlanjwa, Marcia Zikhona (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPA)--Stellenbosch University, 2018.